Ambiguous genitalia with positive reproductive outcome: a case report - Kapadia, Lalit; Kapadia, Rutul; Patel, Manishkumar; Panchal, Yagnik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ambiguous genitalia are an uncommon phenotypic manifestation of the urogenital system that may indicate the presence of a life-threatening underlying disease. The development of normal male or female external genitalia is a consequence of a series of genetic and physiological processes beginning with sex determination and proceeding through internal and external reproductive structure differentiation following the genesis of a zygote. While the failure to progress normally through the stages of sex determination and differentiation is referred to as a disorder of sex development (DSD), not everyone with DSD has ambiguous genitalia. As a result, it is critical to ascertain the etiology as soon as feasible when uncertainty is noticed. The purpose of this case study is to highlight the favorable reproductive result associated with ambiguous genitalia.